Determinant factors of pneumonia among toddlers in Makassar city - Melati Putri Dita; Andi Sitti Rahma; Dewi Setiawati; Darmawansyih Darmawansyih (Malahayati International Journal of Nursing and Health Science, 2023)
Background: Indonesia ranks eighth as a country with cases of childhood pneumonia and ranks second in Indonesia as a cause of death after diarrhea. Based on data from the Makassar City Health Service, the number of pneumonia cases in toddlers in the Bara Baraya Community Health Center area is included in the top three  highest pneumonia cases among all community health centers in Makassar city.Purpose: To determine the relationship between risk factors for pneumonia in toddlers at the  Bara Baraya Community Health Center.Method: This research is analytical research with a case control approach through sampling using a total  sampling technique with 68 samples, consisting of control samples and case samples obtained from medical  records and interviews.Results: In this study, the variable relationship between history of exclusive breastfeeding and pneumonia with a  value of 0.000 (p-value <0.05), relationship between history of exposure to cigarette smoke and pneumonia with  p-value 0.049 (p-value <0.05), relationship nutritional status with pneumonia with a p-value of 0.000 (p-value  <0.05), the relationship between LBW history and pneumonia with a p-value of 0.314 (p-value >0.05), and the  relationship between basic vaccinations and pneumonia with a value p-value 0.076 (p-value >0.05).Conclusion: In this study there are several relationships with the incidence of pneumonia in toddlers, such as exclusive breastfeeding, history of exposure to cigarette smoke, and nutritional status.